2016
DOI: 10.1039/c5dt03387j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of ML and ML2 metal complexes with amino acid substituted bis(2-picolyl)amine ligands

Abstract: Metal complexes with ML or ML2 stoichiometry have been isolated in the reaction of Zn(NO3)2, ZnBr2 or M(NO3)2/NaBF4, M = Zn(ii), Co(ii) or Ni(ii), with either amino acid or amine substituted tridentate nitrogen ligands based on bis(2-picolyl)amine (bpa) or bis(2-quinaldyl)amine (bqa). The stoichiometry (M : L = 1 : 1 or 1 : 2) and stereochemistry (mer, trans-fac or cis-fac) of the products have been studied by NMR and IR spectroscopy, X-ray single crystal analysis and quantum-chemical calculations with an impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 60 publications
1
36
0
Order By: Relevance
“…The addition of KI converts the chloroacetamides to more reactive iodoacetamides, accelerating the reaction. 20 The second synthetic step was initially attempted according to a previously reported procedure, 15,16 by nucleophilic substitution in acetonitrile using potassium carbonate as a base, resulting in a mixture of mono-and disubstituted amine. Ligand L1 was obtained in moderate yield (41%) due to low solubility of the intermediate, monosubstituted amine in acetonitrile, which precipitates from the reaction mixture and is not available for further substitution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of KI converts the chloroacetamides to more reactive iodoacetamides, accelerating the reaction. 20 The second synthetic step was initially attempted according to a previously reported procedure, 15,16 by nucleophilic substitution in acetonitrile using potassium carbonate as a base, resulting in a mixture of mono-and disubstituted amine. Ligand L1 was obtained in moderate yield (41%) due to low solubility of the intermediate, monosubstituted amine in acetonitrile, which precipitates from the reaction mixture and is not available for further substitution.…”
Section: Resultsmentioning
confidence: 99%
“…, indicate a strong Zn─N bond, while broad signals of the corresponding ML2 complexes show a weaker bond and a Zn─N cleavage/coordination kinetics faster than the NMR timescale. 15,30 As the Zn─N bond weakens, nitrogen inversion is enabled and α-CH2 protons are magnetically equivalent. To further study this assumption, variable temperature (VT) NMR was recorded for ML and ML2 complexes of L1 and Zn 2+ .…”
Section: Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way all of the reported computational data correspond to the gas-phase Gibbs free energies at a temperature of 298.15 K and a pressure of 1 atm. The choice of such a computational setup was prompted by our recent success in modeling the properties of gelator molecules [23] and metal binding affinities [24], as well as correctly reproducing thermodynamic and kinetic parameters of organic [25,26] and enzymatic [27] reactions. In order to circumvent problems with the flexibility of the investigated systems, we tried many different conformations in each studied case and report here the results corresponding to the most stable structures.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The idea was to induce metal-binding to modify the gel behavior. Thus far, the available research on coordination geometries between BPA and Zn 2+ have reported mainly tetrahedral, square pyramidal, trigonal bipyramidal, and octahedral structures [ 48 , 49 , 50 , 51 , 52 ]. Having those varieties indicates that the coordination number of the complex and the ligand-to-metal ratio could significantly influence the self-assemblage orientation of the molecules.…”
Section: Introductionmentioning
confidence: 99%